Sistem Kendali Perangkat Listrik dan Monitoring Daya Listrik Berbasis Internet Of Things. - Permana, Baiq Andriska Candra; Muhammad Sadali; Aris Sudianto; Harianto; Lalu Kerta Wijaya (Infotek: Jurnal Informatika dan Teknologi, 2024)
Electricity is one of the basic needs of everyday life. Nowadays, humans are heavily dependent on the availability of electricity, where a stable power supply is essential for lighting and operating various electronic devices. The average electricity consumption of the Indonesian population continued to increase every year during the period 1971–2022. That's a straightforward comparison to the ever-increasing electricity tariff. One attempt to save on the cost of electricity use, for example, is to use it wisely. The research aims to make it easier for users to control electrical devices and monitor the use of electricity at home even when they are not there. The method used is the Internet of Things (IoT) and Blynk technologies that installed on smartphones connected to the Internet. The research results show that users can control electrical devices at home and monitor the power used at home remotely only through their smartphones, as long as their smartphone has an internet connection. With the control and monitoring system, it will be easier for users to manage electricity usage and address instances of electricity wastage caused by user negligence in turning off the electricity when leaving the house